2017
DOI: 10.1038/pr.2017.202
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells of extremely premature infants display impaired immune response after proinflammatory stimulation

Abstract: BackgroundEndothelial cells (ECs) exert immunological functions such as production of proinflammatory cytokines/chemokines as well as facilitation of extravasation of immune cells into infected tissue. Limited data are available on the functionality of ECs from extremely preterm neonates during infection. Accordingly, the aim of our study was to investigate the immune response of premature ECs after proinflammatory stimulation.MethodsCell adhesion receptors' expression and function, nuclear factor 'kappa-light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…We have already taken advantage of this approach in our previous paper to con rm the increased eNOS expression in female ECs [14]. However, the collection of twin cords is limited by a number of criticisms: i) the incidence of spontaneous dizygotic twinning is quite low, around 1-2%; ii) the rate of preterm labour among twins is around 60%; iii) remarkably, HUVECs from premature cords show impaired properties when compared to cells from term cords [72]; iv) intrauterine growth restriction is increased in twin pregnancies [71]; v) about 75% of twins being delivered by cesarean [73]; vi) when childbirth is vaginal, a correlation between twin-to-twin delivery intervals and pH in umbilical arterial blood gas has been found, thus alerting about metabolic acidosis [74]. In addition, it should be considered that some differences may exist between the prenatal environment of male and female dizygotic twins.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…We have already taken advantage of this approach in our previous paper to con rm the increased eNOS expression in female ECs [14]. However, the collection of twin cords is limited by a number of criticisms: i) the incidence of spontaneous dizygotic twinning is quite low, around 1-2%; ii) the rate of preterm labour among twins is around 60%; iii) remarkably, HUVECs from premature cords show impaired properties when compared to cells from term cords [72]; iv) intrauterine growth restriction is increased in twin pregnancies [71]; v) about 75% of twins being delivered by cesarean [73]; vi) when childbirth is vaginal, a correlation between twin-to-twin delivery intervals and pH in umbilical arterial blood gas has been found, thus alerting about metabolic acidosis [74]. In addition, it should be considered that some differences may exist between the prenatal environment of male and female dizygotic twins.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…ECs isolated from fetuses up to 22 weeks of gestational age do not express P-selectin, and intracellular storage of P-selectin in preterm neonates is less than half that of term neonates, at steady state; this, in turn, contributes to the observed defect in rolling, adhesion and crawling of neonatal neutrophils (72). Similarly defective up-regulation of inducible E-selectin, ICAM-1 and VCAM-1 upon LPS stimulation of human umbilical vein ECs (HUVECs) from preterm neonates has been noted (73, 74). Of note, it has also been shown that endothelial selectins, E-selectin and P-selectin, are expressed at least partially during fetal development in humans: in particular, P-selectin seems expressed at adult levels since 11 weeks of gestation while, interestingly, E-selectin reaches adult levels on ECs around 32 weeks (75).…”
Section: Structure Of the Ve In Adults And Neonatesmentioning
confidence: 91%
“…Although the HUC is formed during the fifth week of gestation, the bioenergetic capacity and immune response of HUVEC, obtained from preterm (<37 weeks of gestation) and full-term infants (37-40 weeks of gestation), are different [60][61][62][63][64]. HUVEC, obtained from preterm infants, show an impaired mitochondrial bioenergy capacity, and increased production of reactive oxygen species (ROS) [64].…”
Section: Umbilical Cord Collection and Conservationmentioning
confidence: 99%
“…Illsinger et al demonstrated that HUVEC mitochondrial enzyme activity changes lead to decreased viability of cells obtained from preterm cords [62]. In addition, the expression of selectins is lower in preterm HUVEC as compared to full-term HUVEC [60,61,63]. All these alterations affect endothelial function [60][61][62][63][64].…”
Section: Umbilical Cord Collection and Conservationmentioning
confidence: 99%
See 1 more Smart Citation